Agency cost: A missing link between female on board and firm performance. Issue 3 (9th February 2022) - Khuong, Nguyen Vinh; Anh, Le Huu Tuan; Quyen, Pham Nhat; Thao, Ngo Thi Thien
Abstract: This research aims to investigate the relationship between the presence of females in the board of directors (BOD) and agency cost as well as firm performance with the mediating role of agency costs. We employ STATA to test feasible general least squares and generalized method of moments (GMM) on Vietnamese listed firms' data over 2015–2019. The results demonstrate that the presence of female directors is positively related to firm performance. The percentage of females has a positive relationship with agency cost, which has a negative impact on firm performance. The mediating role of the agency cost variable only reduces the positive impact of gender diversity in the BOD on firm performance, but this relationship is not reversed. The main contribution is the examination of the moderating role of state ownership and the mediating role of agency costs. Our study provides evidence about women's roles in different legal contexts, which might foster the formation of future legal frameworks.